Pengaruh Faktor Personal, Faktor Organisasional, Dan Faktor Non Organisasional Terhadap Komitmen Organisasi (Pada Driver Grab di Kecamatan Lowokwaru Malang) - Mudasir Mudasir; Rois Arifin; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe variables used in this study are personal factors, organizational factors, and non-organizational factors. The research objective is to describe the Organizational Commitment which includes Personal Factors, Organizational Factors and Non-Organizational Factors at Grab Drivers in Lowokwaru District Malang, to identify and analyze the significant influence of Personal Factors, Organizational Factors and Non-Organizational Factors simultaneously or partially on Organizational Commitment. driver Grabin Lowokwaru Malang District. The population in this study is thecommunity driver restoin the District of Lowokwaru Malang, amounting to 90 drivers. The sample in this study amounted to 90 respondents. The sampling technique used in this research is saturated sampling technique. The data analysis method used is the Instrument Test, Multiple Linear Analysis, Hypothesis Test and Coefficient of Determination. From the results of the description analysis, it is concluded that in general the respondents agree with Personal Factors, Organizational Factors and Non-Organizational Factors also have a high enough Organizational Commitment, but in this study Non-Organizational Factors have no significant effect on Organizational Commitment. Based on the results of the Multiple Linear Regression Analysis, it can be seen that the Sig. from non-organizational factors of 0.818> 0.05. In the t test, it was concluded that personal factors, organizational factors and non-organizational factors simultaneously affected Organizational Commitment with the Sig. equal to 0.00 <0.05. This is evidenced by the coefficient of determination of the adjusted R Square value of 161, which means that the dependent variable has a contribution of 16.1% to the independent variable. As for partially but not significant effect on Non-Organizational Factors on Organizational Commitment as evidenced by each Beta coefficient on the t test for Personal Factors (0.325), Organizational Factors (0.252), Non-Organizational Factors (0.025) have no significant effect on Organizational Commitment. on the driver Grab in Lowokwaru Malang District.  Keywords: Personal Factors, Organizational Factors, Non-Organizational Factors and Organizational Commitment.